Effects of some phosphorus sources and liming on peanut production - Nakagawa, João; Nakagawa, Júlio; Imaizumi, Issão; Rossetto, Cláudia A. V. (Pesquisa Agropecuaria Brasileira, 1993)
The effects of simple superphosphate, hyperphosfate, yookarin, termophosphate (yoorin) and partly acidulated phosphate, with and without limestone, on pod and seed yield, yield and seed quality of peanut (Arachis hypogaea L.) cv. Tatu were studied. The limestone was applied to increase the base saturation (V) until 70%; the doses of N - P2O5 - K2O used were 20, 100 and 30 kg/ha. Four experiments were carried out under field conditions, during two years, in the wet and in the dry season crop, in three localities of São Paulo, Brazil. hi 1987/88, the thermophosphate produced the highest pod and seed yield, while in 1988/89, the yields were not affected by fertilizers. In 1987/88, the limestone presence resulted in the highest pod yield for all phosphatic fertilizers, while for seed yield liming was benefic only to simple superphosphate and yookarin. In 1988/89, the liming effect was residual. The liming presented more effects on the yield components than the ferfilizers. The limestone presence yielded seeds with higher germination and vigor than in absence, as immediate effect.
Keywords: Arachis hypogaea; phosphatic fertilizer; pod yield; seed yield; yield components; seed germination; seed vigor